Concurrent treatment with simvastatin and NF-κB inhibitor in human castration-resistant prostate cancer cells exerts synergistic anti-cancer effects via control of the NF-κB/LIN28/let-7 miRNA signaling pathway. - Minyong Kang; Kyoung-Hwa Lee; Hye Sun Lee; Chang Wook Jeong; Ja Hyeon Ku; Hyeon Hoe Kim; Cheol Kwak (PLoS ONE)
We examined the anti-cancer effects and molecular mechanism of simvastatin in human castration-resistant prostate cancer (CRPC) cells, particularly focused on LIN28B and its target molecule, let-7 microRNA (miRNA) among the various target genes of NF-κB. A human CRPC cell line (PC3) was used in the current study. Gene expression patterns were evaluated using real time-PCR and western blot analysis. CCK-8 assay was used for assessing cell viability and proliferation, and a clonogenic assay was adopted to evaluate clonal proliferative capabilities. Induction of apoptotic cell death was analyzed via flow cytometry. Small interfering RNA (siRNA) and short-hairpin RNA (shRNA) were used for manipulating the expression of genes of interest. PC3 showed relatively higher expression levels of LIN28B and lower expression levels of let-7 miRNAs. Simvastatin treatment significantly inhibited cell viability and clonal proliferation in a dose-dependent manner. Importantly, the downregulated let-7 miRNA family was restored after simvastatin treatment. We further observed that human CRPC cells transfected with LIN28B-siRNA or shRNA also showed upregulated let-7 miRNAs. Finally, dual treatment with simvastatin and an NF-κB inhibitor (CAPE) synergistically induced apoptotic cell death, along with reduction of LIN28B expression, and restoration of let-7 miRNAs levels. Our data illustrate that simvastatin remarkably inhibits the growth of human CRPC cells by suppressing NF-κB and LIN28B and subsequently upregulating let-7 miRNAs. Moreover, concurrent treatment with simvastatin and an NF-κB inhibitor synergistically suppressed the growth of human CRPC cells, suggesting a novel therapeutic approach for human CRPC treatment.